التوزيع الجغرافي للصناعات الخدمية وانماطها الموقعية في مدينة كويه - سعيد, كامران طاهر; أسماعيل, احمد جليل; رسول, زيار خضر (Sulaimani Journal for Humanities, 2021)
Service industries are classified as one of those industries that are related in size and size to the city's population, the size of its economies, and the extent of its various activities, despite its importance in most joints of the movement in the city, but the International Classification of Economic Activity (ISIC) classifies it as a category of non-core industrial activities (secondary or complementary) Within the city, it includes a large and different group of maintenance, repair, and maintenance services for everything related to car repair services, appliances, and household necessities, as well as some of the complementary craft activities such as carpentry, sewing, and the production of some household appliances. The importance of the study comes through the great importance of the service industries, and despite it being small and individual industries distributed in most of the city's districts, it is of great importance in the economic movement of civilization, as it is one of the basic and complementary aspects of most other economic activities through the availability of services and industrial goods. Not to mention its importance in providing job opportunities for a large category of employment within cities The study relied on its methodology on two approaches. The first is an inductive fact-based approach based on data related to industrial activity, analysis and evaluation. As for the second, the functional approach through taking service industries as a subject of the study as it is an important part of the industrial function within cities, as well as using some quantitative methods and methods with the aim of Carrying out analyzes, comparisons, and linking study variables with scientific findings. Among the most prominent results of the study is that there is a strong direct correlation between the population and the number of workshops for service industries in the study area, where the value reached (0.98) according to the Pearson correlation coefficient, and there are four basic patterns of service industries that come at the forefront of industrial services for vehicles (48.5 Followed by industrial services related to blacksmithing and carpentry (19.6%), and then industrial engineering services and home appliances repair (16.5%), and finally textile and leather industrial services at a rate of (15.4%), and industrial services in the city take the form of a distribution similar to the regions or sectors according to their quality and nature And its sizes, so that the planned industrial zone occupies more than half of the number of workshops (51.4%), followed by the Central Business District (23.6%), then the commercial streets of the President (13.9%) and finally the service industries inside the residential areas 11.1%).( The research consists of three main axes, in addition to the introduction, results, and proposals. The first axis dealt with the origin and development of service industries and their relationship to population growth in the city of Koya, while the second analyzed the industrial structure of service industries in the city of Koya, and the third axis touched on the site patterns of service industries in the city of Koya.
Keywords: (service industries; industrial structure; site patterns; industrial land uses; city industries; industrial workshops)